Mad Max. Fury road [videorecording (Blu-Ray)] - Miller, George, 1945 March 3-; McCarthy, Brendan; Lathouris, Nico; Hardy, Tom, 1977-; Theron, Charlize; Hoult, Nicholas, 1989-; Keays-Byrne, Hugh, 1947-2020; Helman, Josh; Jones, Nathan, 1969-; Huntington-Whiteley, Rosie, 1987-; Kravitz, Zoë, 1988-; Keough, Riley, 1989-; et al. (Warner Home Video, 2015)
Set in a post-apocalyptic world, Max Rockatansky, haunted by his turbulent past, believes the best way to survive is to wander alone. But he becomes swept up with a group fleeing from Immortan Joe, a ruthless dictator, across the Wasteland in a War Rig driven by an elite Imperator, Furiosa.